(untitled) (Journal of Oriental Studies, 2021)
After the recent events in Afghanistan, the Central Asian countries, as well as other countries, had to change their foreign policy. The seizure of power by the Taliban in Afghanistan affected the current situation in the region. On the one hand, the Central Asian region has a number of local problems, and on the other hand, it is a battleground for influential players. While China seeks to increase its influence in the region in all areas, Russia intends to use new geopolitical games in the region to restore its weakening influence in the region. In this regard, the Central Asian countries need to define a new joint responsibility for mutual relations in the region with countries familiar to them, such as the Russian Federation or the People’s Republic of China. The main purpose of the article is to identify the difficulties and common interests of cooperation between China and the Central Asian countries in the field of religious security and to outline mutually beneficial concepts for further development. It is very important for the People’s Republic of China to maintain security and stability in the Central Asian region. Maintaining stability in the region is necessary not only from the point of view of economic interests, but also in order not to disrupt the internal peace of the state. The presence of Muslim peoples in Xinjiang Uygur Autonomous Region, including unresolved opposition to the central government, the creation of the Islamic State of Afghanistan too close to its sphere of influence, as well as their historical, ethnic and, most importantly, religious unity is one of the key problems for China. Chinese leaders intend to use the Central Asian region as a "buffer" to prevent the penetration of religious extremism and radical movements into their territory. This is one of the main goals in the field of religious security in both bilateral relations and multilateral relations within the framework of the Shanghai Cooperation Organization.